Advanced design and manufacturing technology I : special topic volume with invited papers only - Guo, Hun; Dunwen, Zuo; Guoxing, Tang (Advanced materials research, 2011)
"The major topics covered by the special volumes include manufacture and production, engineering materials, CAD/CAM/CAE, robotics, automation and control, environment-friendly design and manufacture, web/internet technologies, artificial intelligence and smart computing in design and manufacture, enterprise, management, and other related topics"--Preface.